A moderate-length exercise training intervention reduces serum protein status in older adults - García Suárez, Patricia Concepción (2020)
Purpose: To determine the effect of a moderate-length exercise program on metabolic and protein status older adults. Methods: Thirty-five volunteers (age= 62.6±7.3 yr., BMI= 28.3±3.9 kg/m2, Body fat = 39.8±7.1%) completed the exercise program. Measures of body composition (body fat, BMI, muscle mass [MM] and muscle index [Mindex]), serum total proteins (TP), albumin (ALB), glucose (GLU), triglycerides (TG), total cholesterol (TC), 6-min walking test (6MWT), and estimated VO2max were recorded before and after completion of the program. Each training session was performed for 50-min at moderate intensity (12 to 14 on Borg’s RPE scale), with three-days of aerobic exercise and two-days of resistance training, accumulating five sessions per week for 12 weeks. Paired Student’s t-tests with Cohen’s d effect sizes were computed on JASP v0.9.2 software. Results: No significant changes were observed on BMI (Pre= 28.3 ± 3.9 vs. Post= 28.6 ± 4.2 kg/m2, p= 0.067, d= -0.35), body fat (Pre= 39.8 ± 7.1 vs. Post= 40.1 ± 7.4%, p= 0.63, d= -0.09), MM (Pre= 22.7 ± 4.1 vs. Post= 22.8 ± 4.1 kg, p= 0.15, d= -0.27), Mindex (Pre= 9.1 ± 0.9 vs. Post= 8.0 ± 3.1 kg/m2, p= 0.059, d= 0.34), TC (Pre= 183.2 ± 68.9 vs. Post= 175.8 ± 115 mg/dL, p= 0.70, d= 0.06), 6MWT distance (Pre= 480.7 ± 105.7 vs. Post= 461.8 ± 123.6 m, p= 0.9, d= 0.02) and VO2max (Pre= 29.4 ± 6.9 vs Post= 28 ± 7.1 mL•kg-1•min-1, p= 0.46, d= 0.13). Significant reductions were found on GLU (Pre= 98.0 ± 54.4 vs. Post= 77.5 ± 45.3, p= 0.011, d= 0.45), TG (Pre= 122.2 ± 82.0 vs. Post= 99.5 ± 66.5 mg/dL, p= 0.05, d= 0.34), TP (Pre= 6.5 ± 2.6 vs. Post= 4.3 ± 1.5 mg/dL, p= 0.0001, d= 0.90), and ALB (Pre= 3.7 ± 1 vs. Post= 2.9 ± 0.9 mg/dL, p= 0.0001, d= 0.80). Conclusion: A moderate-length 12-week exercise program improved GLU and TG levels in older adults. The lowered TP and ALB with a concomitant trend of the Mindex reduction suggest a metabolic overreaching tending to undernutrition after the program.